Geochemistry of Holocene Black Sea sediments - Michael A Arthur; Walter E Dean (PANGAEA, 2016)
Dating of sediments collected in gravity cores during Leg 1 of the 1988 R/V Knorr expedition to the Black Sea suggests that the onset of water-column anoxia at ~7.5 ka was virtually synchronous across the basin over a depth range of ~200–2250 m. A finely laminated, organic carbon (OC) rich sapropel (unit II) was produced as a result of this anoxia. The trigger for increased OC production and development of anoxia was the spillover of saline waters through the Bosporus that probably began at ~9.0 ka and peaked between ~7.0 and 5.5 ka. This spillover enhanced vertical mixing and nutrient cycling and caused a short-term (2–3 kyr) burst in surface-water productivity during the early part of unit II deposition. Continued incursion of saline waters enhanced vertical stability and inhibited mixing of nutrients into surface waters, thus limiting primary production and decreasing the OC flux to sediments beginning ~5.5 ka. Concentration, accumulation rate, and degree of preservation of organic matter all decreased in the upper part of unit II as a result of decreasing productivity, but anoxia persisted throughout most of the water column. The end of unit II sapropel deposition was synchronous across the Black Sea as the result of the first blooms of the coccolith Emiliania huxleyi, which presumably marked an increase in surface-water salinity above 11 and the beginning of unit I deposition. The high coccolith-carbonate fluxes that occurred during deposition of unit I diluted the OC concentration in the sediments, but OC accumulation rates are about the same as those in upper part of unit II.
Supplement to: Arthur, MA; Dean, WE (1998): Organic-matter production and preservation and evolution of anoxia in the Holocene Black Sea. Paleoceanography, 13(4), 395-411, https://doi.org/10.1029/98PA01161